Association between APOE polymorphisms and lipid profile in Mexican Amerindian population. Issue 11 (26th September 2019) - Martínez‐Magaña, José J.; Genis‐Mendoza, Alma D.; Tovilla‐Zarate, Carlos A.; González‐Castro, Thelma B.; Juárez-Rojop, Isela Esther; Hernández‐Díaz, Yazmín; Martinez‐Hernandez, Angélica G.; Garcia‐Ortíz, Humberto; Orozco, Lorena; López‐Narvaez, María L.; Nicolini, Humberto
Abstract: Background: Apolipoprotein E (ApoE) is a glycoprotein that plays an important role in lipid homeostasis at both cerebral and systemic levels. Moreover, the differential distribution of APOE gene alleles among different populations, means that ApoE isoforms could have different effects on lipids metabolism. The present study aims to evaluate the relationship between APOE gene alleles and the lipid profile in a Mexican Amerindian (MA) population. Methods: This study included 1997 MA individuals of different ethnicities distributed throughout different states of Mexico. All individuals underwent anthropometric measurements as well as laboratory tests including fasting glucose (FG), total cholesterol (TC), triglycerides, low‐density lipoprotein cholesterol (LDL‐C), and high‐density lipoprotein cholesterol (HDL‐C). TaqMan ® probe genotyping assays were used to genotype APOE . The Kruskal–Wallis test was performed to determine the correlation between APOE gene alleles and genotypes and the biochemical variables measured. Results: Among the biochemical variables analyzed, only the HDL‐C and LDL‐C levels showed statistical differences ( p ‐value < .05) between individuals carrying different APOE alleles. For HDL‐C, individuals carrying the E2 allele had higher HDL‐C levels, followed by individuals carrying the E3 allele and carriers of the E4 allele presented the lowest levels of HDL‐C (E2 > E3 > E4). This relationship was inversed for LDL‐C levels (E2 < E3 < E4). Nevertheless, the difference of HDL‐C levels between APOE‐E3 and APOE‐E4 carriers remained only in obese individuals. Conclusions: Our results suggest that APOE gene genotypes play an important role in the differential modulation of lipid profiles in the MA population with obesity. Abstract : We evaluate the relationship between APOE gene alleles and the lipid profile in a Mexican Amerindian population. For HDL‐C, individuals carrying the E2 allele had higher HDL‐C levels, followed by individuals carrying the E3 allele. Carriers of the E4 allele presented the lowest levels of HDL‐C (E2 > E3 > E4).